Total ankle arthroplasty via lateral transfibular approach with and without concomitant subtalar arthrodesis - Serban A. Constantinescu; Agustin Barbero; Carla Carfi; Nicholas Crippa Orlandi; Chiara Bonzano; Cristian Indino; Camilla Maccario; Federico G. Usuelli (The Bone & Joint Journal, 2026)
Aims Concomitant subtalar pathology may require arthrodesis at the time of total ankle arthoplasty (TAA), yet direct comparisons of isolated TAA versus TAA + subtalar joint arthrodesis (STJA) via a lateral transfibular approach, using the same implant, remain limited. We compared ≥ five-year radiological, functional, and range of motion (ROM) outcomes. Methods This retrospective single-centre cohort included 119 patients from January 2015 to December 2020 with ≥ five-year follow-up: 50 underwent TAA with concomitant subtalar arthrodesis and 69 underwent isolated TAA. Outcomes were Foot and Ankle Outcome Score (FAOS), visual analogue pain scale (VAS), 12-Item Short-Form Health Survey questionnaire physical component/mental component summary (SF-12 PCS/MCS), ankle ROM, radiological alignment (lateral distal tibial angle, α, tibiotalar surface (TTS), and Saltzman alignment), and complications. Analyses were performed using Welch’s t -test or the Mann-Whitney U test for continuous variables and the chi-squared test or Fisher’s exact test for categorical variables, together with multivariable regression, using a two-sided significance level of α = 0.05 with Holm correction across angles. Post hoc minimum detectable effect (MDE) analysis at 80% power used observed SDs and group sizes. Results Ankle osteoarthritis (OA) + STJ OA had worse baseline FAOS (24.8 (7.0) vs 42.6 (8.8); p < 0.001), higher VAS (8.4 vs 7.2; p < 0.001), and lower ROM; there was no difference in SF-12 scores. At five years, both cohorts improved; between-group differences in PROMs and ROM were not significant. Radiologically, α and Saltzman alignment were similar; TTS differed modestly (−0.83° (95% CI −1.44 to −0.22); p = 0.048). Subtalar arthrodesis showed radiological bridging in 96% of patients (n = 48). Adjusted models showed no independent STJ effect and no smoking effect. MDE at 80% power was ~4.5 FAOS points (d = 0.52); the observed −3.4-point difference was below the threshold. Conclusion TAA + STJ achieved comparable five-year functional, pain, and radiological outcomes to isolated TAA via the transfibular approach, supporting the safety of this combined approach in selected patients. Cite this article: Bone Joint J 2026;108-B(9):1154–1161.